2004
DOI: 10.1021/ef0499067
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Useful Hydrocarbons from Petroleum Residual Oil by Catalytic Cracking with Steam over Zirconia-Supporting Iron Oxide Catalyst

Abstract: To reduce the consumption of hydrogen when converting heavy oil to light oil, the catalytic cracking of a heavy oil (residue of atmospheric distillation) with steam was examined. Two iron oxide-based catalystsshematite (R-Fe 2 O 3 ) and goethite (FeOOH, denoted herein as FeO X catalyst)swere used. It was found that the heavy oil was converted to a mixture of useful light hydrocarbons (i.e., gasoline, kerosene, and gas-oil) over iron oxide-based catalysts. Moreover, because the FeO X catalyst possessed mesopore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 15 publications
1
73
0
1
Order By: Relevance
“…On the other hand, the Pathway II and aldehydes yields maintained approximately 12 mol%-C and 7 mol%-C, respectively, over 6 h. For the further study of this 5 result, the K content in K[5]/ZrO 2 -FeO X after the catalytic reaction was investigated with an X-ray fluorescence analyzer in our laboratory. It confirmed that the K content still maintained 5 mol% of the total Zr and Fe after the catalytic reaction for 6 h. This well explained the stable yields of the Pathway II and aldehydes over 6 h. [24][25]. Such change in the crystal phase of the catalyst should be responsible for the reduced catalytic activity and the decreased glycerol conversion and allyl alcohol yield.…”
Section: Stability Of K-supported Feo X Catalystsupporting
confidence: 55%
See 2 more Smart Citations
“…On the other hand, the Pathway II and aldehydes yields maintained approximately 12 mol%-C and 7 mol%-C, respectively, over 6 h. For the further study of this 5 result, the K content in K[5]/ZrO 2 -FeO X after the catalytic reaction was investigated with an X-ray fluorescence analyzer in our laboratory. It confirmed that the K content still maintained 5 mol% of the total Zr and Fe after the catalytic reaction for 6 h. This well explained the stable yields of the Pathway II and aldehydes over 6 h. [24][25]. Such change in the crystal phase of the catalyst should be responsible for the reduced catalytic activity and the decreased glycerol conversion and allyl alcohol yield.…”
Section: Stability Of K-supported Feo X Catalystsupporting
confidence: 55%
“…Our previous works 10 consider that ZrO 2 -FeO X has an ability to decompose H 2 O molecules into active hydrogen species [23,25]. These active hydrogen species can act as the hydrogen atoms derived from formic acid and play an important role for the formation of allyl alcohol.…”
Section: Catalytic Reactions Over Alkali Metal-supported Zro 2 -Feo Xmentioning
confidence: 99%
See 1 more Smart Citation
“…After developing catalysts composed of iron oxide (abbreviated FeO X ) supported on 5 zirconia (ZrO 2 ), alumina (Al 2 O 3 ), and ceria (CeO 2 ) (CeO 2 -ZrO 2 -Al 2 O 3 -FeO X , abbreviated as "FeO X -based catalyst"), we succeeded in producing lighter components from atmospheric residual oil (AR) by catalytic cracking in a steam atmosphere [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the growth of oil sand exploitation will exceed 2 to 3 times than the conventional crude oil production. Moreover, better methods are needed to upgrade partially the heavy crude oil before further processing in refineries in order to convert it into light crude oil [4]- [7].…”
Section: Introductionmentioning
confidence: 99%